2016
DOI: 10.1186/s12917-016-0780-y
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoptic mange in the Scandinavian wolf Canis lupus population

Abstract: Background: Sarcoptic mange, a parasitic disease caused by the mite Sarcoptes scabiei, is regularly reported on wolves Canis lupus in Scandinavia. We describe the distribution and transmission of this parasite within the small but recovering wolf population by analysing 269 necropsy reports and performing a serological survey on 198 serum samples collected from free-ranging wolves between 1998 and 2013. Results: The serological survey among 145 individual captured Scandinavian wolves (53 recaptures) shows a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 49 publications
0
5
1
Order By: Relevance
“…In the Iberian Peninsula, in 2004–2008, seroprevalence in Asturias averaged 20.5%, similar to our estimate [ 13 ]. The seroprevalence detected in our study was higher than that reported for Scandinavian wolves (10.1%) during 1998–2013, which was hypothesized to be related to higher densities of wild carnivores and greater contact of wolves with domestic animals in the Iberian Peninsula [ 35 ].…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…In the Iberian Peninsula, in 2004–2008, seroprevalence in Asturias averaged 20.5%, similar to our estimate [ 13 ]. The seroprevalence detected in our study was higher than that reported for Scandinavian wolves (10.1%) during 1998–2013, which was hypothesized to be related to higher densities of wild carnivores and greater contact of wolves with domestic animals in the Iberian Peninsula [ 35 ].…”
Section: Discussioncontrasting
confidence: 72%
“…Most of Europe’s wolf populations have been increasing, however the Iberian population is, in general, stable [ 28 ]. Inhabiting a largely human-dominated landscape, such as our study area [ 47 ], frequent contact with humans and domestic animals may contribute to the occurrence of sarcoptic mange outbreaks [ 1 , 35 ]. Additionally, the Iberian wolf population is highly structured, presents low connectivity [ 48 ], and exhibits low genetic diversity in the major histocompatibility complex class II locus [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In solitary species, non‐social transmission mechanisms may become relevant. For example, solitary species may have predator–prey encounters (Fuchs et al., 2016; Gakuya et al., 2011), intraguild predation (Kolodziej‐Sobocinska et al., 2014; Linnell et al., 1998) or carrion consumption (Alasaad, Ndeereh, et al., 2012; Andrews, 1983).…”
Section: Transmission Dynamicsmentioning
confidence: 99%
“…This disease is widely distributed around the world and it affects a wide range of mammalian species. Sarcoptic mange has been reported in Eurasian lynx ( Lynx lynx ) [ 1 ], European rabbits [ 2 ], Iberian ibex ( Capra pyrenaica ) [ 3 ] and different wolf populations ( Canis lupus ) [ 4 6 ] in Europe. It has also been reported in coyotes ( Canis latrans ) in North America [ 7 ], wombats ( Vombatus ursinus ) in Australia [ 8 , 9 ] or recently in Kenyan giraffes ( Giraffa camelopardalis reticulata ) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%